ANALYSIS OF SARON MELODY IN THE MUSIC ACCOMPANYING THE BUTO DANCE IN SEPANDAK VILLAGE, SAMBAS DISTRICT - Deni, Deni; Diau, Nurmila Sari; Sagala, Mastri Dihita (Universitas Tanjungpura, 2024)
This research discusses the analysis of the Saron melody in the accompanying music for the Buto dance in Sepandak Village, Sambas Regency. A literature review related to the analysis of the Saron melody as an accompaniment to the Buto Dance will help in understanding how the Saron melody in the accompanying music for the Buto Dance functions as the main melody which has a high pitch, so that the rhythm is played will be better. sounds clearer. The research method uses analytical qualitative and qualitative research forms with musicological and ethnomusicological approaches. Researchers collected data using observation, interviews and documentation techniques. The data source is Mr. Yanto, he has the main knowledge in this research. Results and Discussion 1. General description and research location 2. Social system at the research location 3. Brief history of the music accompanying the Buto dance in Sepoandak Village 4. Analysis of the saron melody in the music accompanying the Buto dance. In Sepandak Village. The research conclusion based on data analysis of the Saron melody shows the characteristics of a melody that is played repeatedly because it does not have a clear tone development, does not have sentences/points (question sentences and answer sentences), only contains one motif , and looks more like harmony of the firm. Suggestions regarding this research require good cooperation between the community and arts practitioners to maintain cultural preservation.